Effects of backrest and seat-pan inclination of tractor seat on biomechanical characteristics of lumbar, abdomen, leg and spine. Issue 3 (17th February 2023) - Wang, Qichao; Huo, Yihuan; Xu, Zheng; Zhang, Wenjie; Shang, Yujun; Xu, Hongmei
Abstract: Seat is a direct human-machine interaction component between the tractor and driver, and thus its reasonable parameter design is of great significance for preventing occupational diseases and improving driving comfort, safety and operation efficiency. In this study, a biomechanical model of seat-driver system was established with the AnyBody biomechanical software. The activities of the lumbar, abdominal and leg muscles and the load of the spine of the driver were used as indicators for quantitative simulation analysis of the inclination of backrest and seat-pan. The results reveal that the optimal range of backrest inclination angle is 3–15°, which contributes to the lowest muscle activity and spinal load of the driver. As for the seat-pan inclination, the activities of lumbar and abdominal muscles and the spinal load generally show slight fluctuations with increasing inclination angle, but there are complex changes in the activities of leg muscles, and the seat-pan inclination angle of 5–16° was determined as the optimal range for better overall driving comfort.